2000
DOI: 10.1002/1521-1878(200101)23:1<3::aid-bies1001>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Oh no, Notch again!

Abstract: The Notch receptor signaling pathway is important for morphogenesis and development of many organs and tissues in most if not all multicellular species. The classical view holds that Notch signaling keeps cells in an undifferentiated state. Recently, however, this notion has been challenged in the nervous system by two sets of observations: Notch plays an active role in the differentiation of glial cells,(1-4) and Notch influences the length and organisation of neuronal processes.(5-7) In this review, we analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Additionally, Jagged1 might activate Notch when receptor‐ligand engagement occurs between neighboring cells. Such cis ‐ and trans ‐dependent differences have been demonstrated for the interaction of Notch with another ligand, Delta, on developing neuronal cells (reviewed in Artavanis‐Tsakonas et al, 1999; Frisen and Lendahl, 2001). Whether analogous multifaceted signaling pathways can occur between Notch1 and Jagged1 in the pulmonary vasculature has yet to be determined.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Additionally, Jagged1 might activate Notch when receptor‐ligand engagement occurs between neighboring cells. Such cis ‐ and trans ‐dependent differences have been demonstrated for the interaction of Notch with another ligand, Delta, on developing neuronal cells (reviewed in Artavanis‐Tsakonas et al, 1999; Frisen and Lendahl, 2001). Whether analogous multifaceted signaling pathways can occur between Notch1 and Jagged1 in the pulmonary vasculature has yet to be determined.…”
Section: Discussionmentioning
confidence: 91%
“…Second, in addition to acting as a “gatekeeper” and restricting the number of cells responding to various inductive cues, the Notch family might also function later in the stabilization and maintenance of a matured system. In neuronal development, for example, Notch signaling functions beyond initial differentiation of glial cells to influence the length and organization of established neuronal processes through successive “pruning” (reviewed in Frisen and Lendahl, 2001). The acquisition we have observed of Notch1 and Jagged1 by maturing vascular structures of the lung during embryonic development, and their persistence in the adult animal, may similarly represent a role in vascular homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of pro‐gliogenic transcription factors may be regulated through cell surface receptors such as notch25. It has been shown that jagged‐1 (a notch ligand) signalling by neurones suppresses the oligodendrocyte phenotype26.…”
Section: An Overview Of Brain Development During Embryogenesismentioning
confidence: 99%
“…Notch is also involved in several other neural lineages where it controls glial vs. neuronal development [84,85,86,87,88,89]. A Notch/Delta/Numb system is similarly used in many asymmetric cell divisions that occur during neural development in Drosophila [90,91,92,93] and Notch has been shown to control neuronal vs. glial fate choices in some of these lineages [94,95].…”
Section: Vervoort and Ledent: Neural Basic Helix Loop -Helix Loop Promentioning
confidence: 99%